Clasification System of Library Book Based on Similarity of The Book Title Using K-Means Method (case Study Library of Bhayangkara Surabaya) - Arif Mardi Waluyo; Eko Prasetyo; Arif Arizal (Fakultas Teknik Universitas Bhayangkara, 2018)
In the grouping of book data in the library of Universitas Bhayangkara Surabaya at this time, the grouping is stillbased on the title and the existing field. So that resulted in the laying of some books whose title is not in accordancewith the field of place. To facilitate the grouping of library books, in this research will provide a solution by doingthe grouping of books based on the similarity of the title using K-Means method with the distance dissmilarity. Thedata are grouped a number of 500 titles in the library of Bhayangkara University Surabaya. The data will beprocessed through the Pre-processing process first of each book title by using the Information Retrieval Systemwhich results in the basic word. The basic word that will be used as a feature in the process of grouping so that canbe known similarity. The result of the research is that it can be concluded that the application of Library BookGrouping System Based on Similarity of Book Title Using K-Means Method (Case Study of Bhayangkara LibrarySurabaya) is suitable for data that has been specified on each title. And some processes there are clusters that arealways consistent in putting the book data in accordance with the similarity. Of all test results that have the bestsilhouette value is on using the value of K = 7, ie in the process to 1 with the value of silhouette = 0.2221